Thailand Islamic Community Perspective Towards the Ratification of LGBTQI++ - Zidan, Muhammad Zainuddin; Iskandarsyah, Muhammad Raditya (KARSA Journal of Social and Islamic Culture, 2024)
The Marriage Equality Bill in Thailand will officially take effect on January 22, 2025. With this enactment, Muslims in Thailand will certainly have perspectives and attitudes concerning the youth in Islam in facing this issue. This study aims to explore the views of Islamic religious teachers regarding students in light of the legalization of LGBTQI++ in Thailand. To gather this information, a questionnaire with a 5-point Likert scale was distributed to 12 Islamic religious teachers at Sasana Business Administration Vocational College in Bangkok. The primary source of this study consists of data from the questionnaire, while secondary sources include relevant research articles that support this research article. The results indicate that almost all Islamic religious teachers are opposed to the enactment of this policy. They believe it will impact students’ identity, characteristics, and religious morality as the young Muslim generation in Thailand. Therefore, they propose plans to provide education on these issues through communication strategies and open discussions.